Thermal-RGB Sensory Data for Reliable and Robust Perception - El Ahmar, Wassim (Université d'Ottawa / University of Ottawa, 2023)
The significant advancements and breakthroughs achieved in Machine Learning (ML) have revolutionized the field of Computer Vision (CV), where numerous real-world applications are now utilizing state-of-the-art advancements in the field. Advanced video surveillance and analytics, entertainment, and autonomous vehicles are a few examples that rely heavily on reliable and accurate perception systems. Deep learning usage in Computer Vision has come a long way since it sparked in 2012 with the introduction of Alexnet. Convolutional Neural Networks (CNN) have evolved to become more accurate and reliable. This is attributed to the advancements in GPU parallel processing, and to the recent availability of large scale and high quality annotated datasets that allow the training of complex models. However, ML models can only be as good as the data they train on and the data they receive in production. In real-world environments, a perception system often needs to be able to operate in different environments and conditions (weather, lighting, obstructions, etc.). As such, it is imperative for a perception system to utilize information from different types of sensors to mitigate the limitations of individual sensors. In this dissertation, we focus on studying the efficacy of using thermal sensors to enhance the robustness of perception systems. We focus on two common vision tasks: object detection and multiple object tracking. Through our work, we prove the viability of thermal sensors as a complement, and in some scenarios a replacement, to RGB cameras. For their important applications in autonomous vehicles and surveillance, we focus our research on pedestrian and vehicle perception. We also introduce the world's first (to the best of our knowledge) large scale dataset for pedestrian detection and tracking including thermal and corresponding RGB images.
Keywords: machine learning; artificial intelligence; object detection; multiple object tracking; perception